Study on the Development of Mobile Learning Promoted by Cloud Computing - Jian Li (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
Cloud computing which is regarded as the next revolution of science and technology is the development of distributed processing, parallel computing and grid computing. It is an Internet-based super computing model and is promoting the rapid development of mobile learning for its unique superiority as well. The paper summarizes the characteristics and models of traditional mobile learning, analyzes the features of cloud computing and clarifies the superiority of development of the mobile learning model in the cloud computing environment.